Penggunaan Pembelajaran Model Kooperatif Tipe Jigsaw sebagai Upaya Meningkatkan Kemampuan Membaca Pemahaman Materi Novel Jawa - Widya Dwi Rahmawati; Aida Yuliawati; Nur Fateah (Piwulang Jurnal Pendidikan Bahasa Jawa, 2024)
The problem raised in this research is the low reading comprehension ability shown by students in Javanese language subjects, especially novel material in class XI TEK 1 SMK Negeri 7 Semarang. The aim of this research is to improve the reading comprehension skills of Class XI TEK 1 students at SMK Negeri 7 Semarang through a jigsaw type cooperative learning model. This research is classroom action research (PTK) which includes two cycles consisting of planning, implementing actions, observing and reflecting. The data collected consists of qualitative data, namely the results of reading comprehension and observation tests, as well as quantitative data obtained from test results which reflect reading comprehension abilities.  Data was analyzed using qualitative and quantitative techniques. The results of this research indicate that the application of the jigsaw type cooperative learning model is categorized as effective in the Javanese language learning process in class XI vocational school. In the pre-cycle, 10 students succeeded. In cycle I 25 students completed and 10 students did not complete, while in cycle II 31 students completed and 4 students did not complete. The percentage of classical learning completeness is 88% in the complete category. This research can be used by teachers as a guide for applying the jigsaw model in learning so that it can improve students' ability to understand novel texts more effectively.